Differential chromatin binding of the lung lineage transcription factor NKX2-1 resolves opposing murine alveolar cell fates in vivo - Danielle R. Little (Nature Portfolio, 2021)
How transcription factors regulate cell fates in native tissues is unclear. Here, the authors report that differential chromatin binding of NKX2-1 determines opposing alveolar cell fates in the murine lung, showing loss of YAP/TAZ directs NKX2-1 to alternative binding sites leading to cell fate conversion.